DALEC – a novel web tool for integrated day- and artificial light and energy calculation. Issue 3 (4th May 2017) - Werner, Matthias; Geisler-Moroder, David; Junghans, Bert; Ebert, Oliver; Feist, Wolfgang
Abstract : DALEC is a novel, combined lighting and thermal simulation web tool. This tool allows building designers to evaluate their individual façade concepts in terms of thermal and visual performance and ultimately their impact on overall building energy use. Although easy to use, the software accounts for the complex thermal and light processes in buildings, by way of sophisticated and time-saving pre-calculations. Based on climatic data a calculation of heating, cooling and electric lighting loads can be obtained within a simulation time shorter than one second. The model has been validated by comparison with experimental data and other state-of-the-art software and shows deviations less than 15%. Not only energy demand is considered, but also user behaviour (e.g. glare protection), as well as visual and thermal comfort. This innovative, holistic approach facilitates and accelerates the design of sustainable and energy-efficient building for new, as well as for refurbished buildings.